2013
DOI: 10.1073/pnas.1310345110
|View full text |Cite
|
Sign up to set email alerts
|

Charge-dependent secretion of an intrinsically disordered protein via the autotransporter pathway

Abstract: Autotransporters are a large class of virulence proteins produced by Gram-negative bacteria. They contain an N-terminal extracellular ("passenger") domain that folds into a β-helical structure and a C-terminal β-barrel ("β") domain that anchors the protein to the outer membrane. Because the periplasm lacks ATP, the source of energy that drives passenger domain secretion is unknown. The prevailing model postulates that vectorial folding of the β-helix in the extracellular space facilitates unidirectional secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 63 publications
3
40
1
Order By: Relevance
“…However, constructs used in that study preserved a significant portion (Ͼ100 residues) from the C terminus of the wild type passenger, including a segment shown previously to be important for passenger folding and OM translocation (9, 10, 39 -41). In addition, many studies have found the AT secretion process to be severely disrupted under conditions that induced passenger folding in the periplasm (10,24,42,43), consistent with our simulation results. On balance, it appears that AT OM translocation can be severely disrupted either by premature folding in the periplasm or by a disruption of folding at the cell surface, particularly in the C-terminal region of the passenger.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, constructs used in that study preserved a significant portion (Ͼ100 residues) from the C terminus of the wild type passenger, including a segment shown previously to be important for passenger folding and OM translocation (9, 10, 39 -41). In addition, many studies have found the AT secretion process to be severely disrupted under conditions that induced passenger folding in the periplasm (10,24,42,43), consistent with our simulation results. On balance, it appears that AT OM translocation can be severely disrupted either by premature folding in the periplasm or by a disruption of folding at the cell surface, particularly in the C-terminal region of the passenger.…”
Section: Discussionsupporting
confidence: 91%
“…At first glance, these results may seem to contradict the recent finding that AT OM translocation is not significantly disrupted in EspP mutants with a largely disordered passenger (24). However, constructs used in that study preserved a significant portion (Ͼ100 residues) from the C terminus of the wild type passenger, including a segment shown previously to be important for passenger folding and OM translocation (9, 10, 39 -41).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Plasmids were maintained by the addition of ampicillin (100 g/ml). Antisera against EspP C-terminal and N-terminal peptides and the purified EspP passenger domain have been described previously (30,31). Purified recombinant tobacco etch virus (TEV) protease (hyperactive S219V mutant) was obtained from Susan Buchanan.…”
Section: Methodsmentioning
confidence: 99%
“…Kang'ethe and Bernstein 42 produced a chimeric protein with a highly acidic receptor-binding domain (RD), to explore the mechanism of secretion. They found that the RD moiety was secreted efficiently when unfolded, but changing the pH stalled translocation.…”
Section: Analyzing the Functions Of Idps And Idprsmentioning
confidence: 99%